PENGARUH KONDISI TANAH ASAM DAN CACAT GORES BERBENTUK PERSEGI PANJANG PADA LAPIS LINDUNG TERHADAP KEBUTUHAN ARUS PROTEKSI SISTEM IMPRESSED CURRENT CATHODIC PROTECTION (ICCP) DENGAN MENGGUNAKAN BAJA AISI 1045 - Tubagus Noor Rohmannudin; Sulistijono Sulistijono; Faris Putra Ardiansyah (Teknoin, 2015)
Corrosion is degradation of the metal due to an oxidation reaction between the metal with many substances that exist in the environment around them and form undesirable compounds. Corrosion can not be prevented, but still can be controlled its speed. One of the corrosion control process in a material can be used a  coating and cathodic protection by providing a forced flow. At this time the research conducted will learn about the effect of the rectangular scratch defect and the acid soil pH to the needs of current protection in the impressed current cathodic protection system (ICCP). The variation of given scratch is rectangular with each area of 10 mm2, 50 mm2, 100 mm2, 150 mm2, 250 mm2 and 500 mm2. While the differences in soil pH use is pH 3, pH 5, and pH 7. Then there is also a specimen without scratch and without layers of protection that is used as a comparison. In the ICCP system installation, AISI 1045 steel is used as the cathode and graphite as the anode. The system used a rectifier that is useful for current rectifier. The flow of the ICCP protection is set such that the value of the potential difference can reach -850 mV against the reference electrode Cu / CuSO4. Measurement of the current protection on the ICCP system performed during the 7 days with daily data retrieval. After obtained the measurement of the current protection value, showed that the greatest current protection value with 500 mm2 defect area in acidic soils (pH 3) that is equal to 1.696 mA. While the smallest current protection in area of 10 mm2 with normal soil that is equal to 0.032 mA. The influence of these two variables were calculated using multiple regression statistical analysis so as to get the equation Y = 0,11 + 0,008 X1 + 0,0004 X2. Where the value of X1 as soil pH conditions, X2 as scratch defect, and Y as current protection.